Dietary micronutrients intake and its effect on haemoglobin levels of pregnant women for clinic visit in the Mount Cameroon health area: a cross-sectional study - Jugha, Vanessa Tita; Anchang, Juliana Adjem; Sofeu-Feugaing, David Denis; Taiwe, Germain Sotoing; Kimbi, Helen Kuokuo; Anchang-Kimbi, Judith Kuoh (Frontiers in Nutrition, 2024)
Nutritional deficiencies and its consequences such as anaemia are frequent among pregnant women residing in under resource settings. Hence, this study sought to investigate specific dietary micronutrient inadequacy and its effect on maternal haemoglobin levels.This institution based cross-sectional survey enrolled 1,014 consenting pregnant women consecutively. Data on socio-demographic, economic and antenatal characteristics were recorded using a structured questionnaire. Minimum dietary diversity for women (MDD-W) was assessed using the 24-hour recall method and haemoglobin (Hb) concentration (g/dL) determined using a portable Hb meter. Significant levels between associations was set at P < 0.05.Among those enrolled, 40.9% were anaemic while 89.6% had inadequate dietary nutrient intake. In addition, uptake of blood supplements, haem iron, plant and animal-based foods rich in vitamin A were 71.5%, 86.2%, 35.5% and 12.6% respectively. Moreover, anaemia prevalence was significantly (P < 0.05) lower in women who took iron-folic acid along with food groups rich in haem iron (38.5 %) or both plant and animal vitamin A (29.0 %). Besides, mean maternal Hb levels was significantly (P < 0.001) higher in women who consumed haem iron (11.08 ± 1.35) and vitamin A food groups (11.34 ± 1.30) when compared with their counterparts who did not consume haem iron (10.54 ± 1.19) and vitamin A food groups (10.74 ± 1.31).Dietary uptake of foods rich in haem-iron and vitamin A significantly improves Hb levels in Cameroonian pregnant women. Our findings underscore the importance of improving maternal nutritional awareness and counselling during antenatal period to reduce the anaemia burden.